Pengaruh budaya organisasi, pengembangan karir dan self efficacy terhadap kinerja karyawan pada PT. Pos Padang - Putri Azizi; Ai Elis Karlinda; Mardhatila Fitri Sopali (Journal of Information System, Applied, Management, Accounting and Research, 2021)
This study aims to determine how much influence Organizational Culture, Career Development, and Self Efficacy have on Employee Performance. The analytical method used is correlation analysis and multiple regression. The method of data collection in this study is to use a questionnaire filled out by respondents, namely employees of PT. Padang Post. From the results of multiple regression analysis, it shows that: (a) organizational culture has a partially significant effect on employee performance, (b) career development has a partially significant effect on employee performance, (c) self-efficacy has a partially significant effect on employee performance development, (d) ) organizational culture, career development and self-efficacy together on career development, (e) the contribution of organizational culture, career development, and self-efficacy variables together on employee performance is 71.4% while the remaining 28.6 % influenced by other variables not examined in this study.